Character association of seeds on plant morphology in Snakegourd (Trichosanthes anguina L.) - Ashok P (Department of Olericulture, College of Horticulture, 2000)
The research project 'Character association of seeds on plant morphology in snakegourd (Trichosanthes anguina L.)' was carried out in College of Horticulture, Kerala Agricultural University, Vellanikkara, Thrissur during the period 1999-2000. The study envisaged to find out the association of various seed characters on the vegetative characters of snakegourd, classification of accessions based on the seed index, growth index and yield index as obtained from principal component analysis and to formulate keys for varietal identification. The 25 accessions were catalogued based on the IBPGR descriptor list. Significant differences for various seed characters, growth characters and yield characters were noticed among the accessions. Correlation studies have shown that the number of seeds per fruit strongly associated with days to male flower opening and fruit maturity. Seed size index was strongly associated with leaf size. The highest seed index value for TAl 08, the highest growth index value for TA 118 and the highest yield index value for TA 114 were obtained as revealed from principal component analysis . . Twenty five accessions were grouped into different clusters based on the seedindex, growth index and yield index. Based upon the seed characters (seed size, seed coat colour and 100 seed weight), growth characters (leaf lobes, leaf pubescence and tendril length) and fruit characters (fruit skin colour, fruit girth, fruit length and fruit weight) keys were developed for varietal identification.